1992
DOI: 10.1021/es00035a007
|View full text |Cite
|
Sign up to set email alerts
|

Development of a structure-reactivity relationship for the photohydrolysis of substituted aromatic halides

Abstract: Rates of photodegradation of 13 structurally related 1,3-di-and 1,3,5-trisubstituted halogenated benzene derivatives in dilute aqueous solution were measured in the laboratory at wavelengths ranging from 250 to 360 nm. As shown by mathematical simulations of the reaction rate constants involved, photohydrolysis of all compounds studied is the main transformation process, generally accounting for over 95% of the amount of starting material removed. Quantum yields of this process were calculated using 3-chloroph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

1994
1994
2014
2014

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 43 publications
(14 citation statements)
references
References 11 publications
(20 reference statements)
0
14
0
Order By: Relevance
“…This procedure is reliable when measuring the rates of fast reactions in aqueous solutions, with overall second-order kinetics, and firstorder with respect to both reactants (the micropollutant and the oxidant). 14,22 By taking these considerations into account, the model proposes the following rate equation for the elimination of the reference compound:…”
Section: Kinetic Study and Prediction Of Elimination Of Pharmaceuticalsmentioning
confidence: 99%
“…This procedure is reliable when measuring the rates of fast reactions in aqueous solutions, with overall second-order kinetics, and firstorder with respect to both reactants (the micropollutant and the oxidant). 14,22 By taking these considerations into account, the model proposes the following rate equation for the elimination of the reference compound:…”
Section: Kinetic Study and Prediction Of Elimination Of Pharmaceuticalsmentioning
confidence: 99%
“…Direct photolysis can take place only if a photon is absorbed by a compound, leading to bond cleavage or rearrangement to form a new, stable product. It was found that most environmental photochemical reactions follow pseudo-®rst-order kinetics (Zepp and Schlotzhauer, 1979;Zepp, 1982;Dulin et al, 1986;Choudhry and Webster, 1989;Peijnenburg et al, 1992;Larson and Weber, 1994). Photolysis rate constants and quantum yields are two key parameters characterizing photochemical reactions of organic pollutants.…”
Section: Introductionmentioning
confidence: 99%
“…With regard to QSPRs on photolysis, in 1992, Peijnenburg et al (1992) reported ®rstly a QSPR model on direct photolysis quantum yields of selected meta-substituted halobenzenes under irradiation of arti®cial light sources. Chen et al (1998) were the ®rst to report on a QSPR model for photolysis rate constants of selected polycyclic aromatic hydrocarbons (PAHs) under irradiation of arti®cial light sources.…”
Section: Introductionmentioning
confidence: 99%
“…This competitive method has been previously used with success by several authors in photochemical studies of organic compounds. 24,25 Thus, and according to the considerations of Peijnemburg et al, 24 the photolysis rate given by eqn (3) also holds when two or more compounds are simultaneously photodegraded. Then the rate expressions for a specific couple of solutes can be written in the form:…”
Section: Direct Photolysis Of Herbicides In Ultrapure Watermentioning
confidence: 92%